Blood gas phenotyping and tracheal intubation timing in adult in-hospital cardiac arrest: a retrospective cohort study - Chih-Hung Wang (Nature Portfolio, 2021)
Abstract To investigate whether the optimal time to tracheal intubation (TTI) during cardiopulmonary resuscitation would differ by different blood gas phenotypes. Adult patients experiencing in-hospital cardiac arrest (IHCA) from 2006 to 2015 were retrospectively screened. Early intra-arrest blood gas analysis, performed within 10 min of resuscitation, was used to define different phenotypes. In total, 567 patients were included. Non-severe acidosis (pH≧7.15) was associated with favourable neurological outcome (odds ratio [OR]: 4.60, 95% confidence interval [CI] 1.63–12.95; p value = 0.004) and survival (OR: 3.25, 95% CI 1.72–6.15; p value < 0.001) in the multivariable logistic regression analyses. In the interaction analysis, normal blood gas phenotype (pH: 7.35–7.45, PCO2: 35–45 mm Hg, HCO3 − level: 22–26 mmol/L) × TTI ≦ 6.3 min (OR: 20.40, 95% CI 2.53–164.75; p value = 0.005) and non-severe acidosis × TTI ≦ 6.3 min (OR: 3.35, 95% CI 1.00–11.23; p value = 0.05) were associated with neurological recovery while metabolic acidosis × TTI ≦ 5.7 min (OR: 3.63, 95% CI 1.36–9.67; p value = 0.01) and hypercapnic acidosis × TTI ≦ 10.4 min (OR: 2.27, 95% CI 1.20–4.28; p value = 0.01) were associated with survival. Intra-arrest blood gas analysis may help guide TTI during for patients with IHCA.